2004
DOI: 10.1149/1.1639165
|View full text |Cite
|
Sign up to set email alerts
|

Microfabrication of Glassy Carbon by Electrochemical Etching

Abstract: Due to the broad impact of microfabrication technology on chemistry and biology, new methods to pattern and etch a variety of materials are being explored in a number of laboratories. We have developed a method for the etching of glassy carbon ͑GC͒ that opens pathways for the creation of new electrode patterns and devices. The method involves standard pattern transfer to a photoresist layer and anodization of the exposed GC substrate in basic electrolyte. The electrode reaction results in a breakup of the carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…[23][24][25] Formation of carbonyl, phenolic groups, lactone, ether, quinine, hydroxyl and carboxyl as a graphite oxide lm has been previously reported. [23][24][25] Formation of carbonyl, phenolic groups, lactone, ether, quinine, hydroxyl and carboxyl as a graphite oxide lm has been previously reported.…”
Section: Fiber Preparationmentioning
confidence: 82%
See 1 more Smart Citation
“…[23][24][25] Formation of carbonyl, phenolic groups, lactone, ether, quinine, hydroxyl and carboxyl as a graphite oxide lm has been previously reported. [23][24][25] Formation of carbonyl, phenolic groups, lactone, ether, quinine, hydroxyl and carboxyl as a graphite oxide lm has been previously reported.…”
Section: Fiber Preparationmentioning
confidence: 82%
“…[23][24][25] Formation of carbonyl, phenolic groups, lactone, ether, quinine, hydroxyl and carboxyl as a graphite oxide lm has been previously reported. This lm increases the electrode surface area 23 and contains many anionic sites, and it is permeable to solvent and small molecules. This lm increases the electrode surface area 23 and contains many anionic sites, and it is permeable to solvent and small molecules.…”
Section: Fiber Preparationmentioning
confidence: 82%
“…Mekaru et al [ 114 ] reported an etch rate of 1.8 nm/s with oxygen and sulfur hexafluoride plasma, which was attributed to the fact that the dry etching of GC material is very slow. Moreover, solution-based chemical etching is rarely utilized for GC mold fabrication because GC exhibits isotropic etching behavior due to its amorphous structure [ 115 ].…”
Section: Mold Materials For Precision Glass Moldingmentioning
confidence: 99%
“…However, FIB milling [ 30 ] and various dry [ 31 ] and wet [ 28 ] etching methods have been effectively used to pattern it. Its exceptional inertness makes the chemical (wet) etching challenging, but an electrochemically assisted wet etch is generally possible [ 28 ], since glassy carbon does exhibit an electrochemical corrosion [ 121 ]. Dry etching is often carried out with the aid of reactive ions and/or high-density plasma.…”
Section: Glassy Carbon Structures and Devicesmentioning
confidence: 99%
“…In addition to the carbonization of patterned polymers, device-compatible micro/nano structures can be realized by directly machining glassy carbon. Although this material is difficult to machine, methods, such as electrochemical [ 28 ] and thermochemical [ 29 ] etching, Focused Ion Beam (FIB) milling [ 30 ], and laser machining [ 31 ] have been employed to pattern it. In this contribution, some recent glassy carbon micro/nano devices fabricated using both strategies are described.…”
Section: Introductionmentioning
confidence: 99%